The paradox of parental influence in Danish schools. A Swedish perspective - Kristoffersson, Margaretha (International Journal about Parents in Education, 2023)
In this article I discuss the boards of compulsory schools in mainly Denmark and Sweden to a less extent where parents are in majority. Questions of interest for my study are: Why is parental interest in being elected to school boards so low? Why do teachers react negatively to questions about school boards? How are the various interests of teachers, pupils, parents and politicians balanced in the actual partnership? What impact do neo-liberalism and marketplace policies have on the participation of parents in schools? All the questions emanate from the paradox that traditional Danish ways of ensuring parental influence no longer seem to work with the current type of school boards. Utilizing concepts from the frame factor theory I explore the consequences of this for school boards. Data collection is designed as case studies and the methods used are interviews, participation in board meetings, school visits and document analysis. The conclusion shows that school boards are complex and even contradictory. Politicians´ aims regarding boards are not clear. Boards cannot be a relevant response to the political threat from private school policy or a general solution to problems of local democracy.